PHARMACOLOGICAL MANAGEMENT OF DEPRESSION AND HALLUCINATIONS IN PARKINSON’S DISEASE: A COMPREHENSIVE REVIEW - Karolina Ryba; Gabriela Godek; Karolina Ochyra; Martyna Bukała; Kornelia Pudło; Jowita Frydrych; Anna Rakoczy; Patrycja Walkiewicz; Katarzyna Znamirowska; Klaudia Zacher (International Journal of Innovative Technologies in Social Science, 2025)
Purpose: The aim of this study is to present available treatment options for depression and hallucinations in Parkinson’s disease (PD). The review discusses the application of serotonin-norepinephrine reuptake inhibitors (SNRIs, e.g., duloxetine), selective serotonin reuptake inhibitors (SSRIs, e.g., paroxetine, escitalopram), pimavanserin, pramipexole, and repetitive transcranial magnetic stimulation (rTMS) in the treatment of depressive symptoms in PD. Moreover, the therapeutic use of atypical antipsychotics such as clozapine, quetiapine, and pimavanserin in managing hallucinations in PD is addressed.Materials and Methods: This review is based on literature identified via Google Scholar.Results and Conclusions: SSRIs are among the most commonly prescribed agents in the treatment of depression associated with Parkinson’s disease, although robust evidence supporting their efficacy in large cohorts remains limited. Other therapeutic options include SNRIs and tricyclic antidepressants. In cases of Parkinson’s disease-related hallucinations, the initial approach involves reducing dopaminergic medication doses to rule out drug-induced psychosis. If symptoms persist, second-generation atypical antipsychotics may be introduced. Clozapine and quetiapine are preferred over agents such as olanzapine and risperidone due to a more favorable motor side effect profile. Pimavanserin stands out as a promising agent due to its minimal adverse effects and high safety profile in this patient population.